PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT PERKEBUNAN NUSANTARA - Wulandari, Wulandari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The research was conducted at PT Perkebunan Nusantara XII (Persero) in order to determine the implementation of Good Corporate Governance and the problems occurred during the implementation The result of research shows that PT Perkebunan Nusantara XII (Persero) awarded as good based on the assessment. The implementation of Good Corporate Governance in the company demonstrated by the implementation of the principles of good corporate governance, the principles of openness with the transparency during the process the Board of Directors appointment through the fit and proper test, the principle of accountability to the clarity of the functions and responsibilities of the companys organs through the organizational structure, the principle of the Responsibility program corporate social responsibility, the principle by appointing an independent auditor which is the Public Accountant Hertanto Sidik and friends to audit the financial statements and the last principle of fairness is shown by the different regulations concerning the management of the company. Some of the obstacles are the absence of transparency in the election of the members on the Board of Commissioners, the system of reward and punishment has not been executed by the company, minutes of meetings do not meet the dynamics of the meeting, it is not yet published the Decree on independent Commissioners, and the annual report of 2010 has not been uploaded yet. Keywords: Good Corporate Governance, Transparency, Accountability, Responsibility, Independent, Fairness.